BLOOD PLASMA UREA CONCENTRATION AND ITS RELATIONSHIP WITH MILK PRODUCTION PARAMETERS IN CZECH PIED COWS - Gustav CHLÁDEK; Ladislav MÁCHAL (Journal of Central European Agriculture, 2005)
Experimental groups of 18 Czech Pied cows were observed in the course of 12 consecutive calendar months in order to describe the relationship between urea concentration in blood plasma and milk production. The cows were in early lactation, the mean number of lactation was 2.6, number of days after calving 55.6 and concentration of urea in blood plasma 5.42 mmol/l. During the fi rst 100 days of lactation milk yield amounted to 2624 kg with 3.90 % fat, 3.47 % protein and 4.86 % lactose. The calculated coefficients of the correlation between blood plasma urea concentration and milk production parameters greatly varied between test days and thus did not reveal any clear relationships. Graphic polynomials expressed the relationships better. They showed that urea concentration in blood plasma tended to have a significant positive relationship with milk fat content, and a significant negative relationship with milk protein content. The relationships between urea concentration and number of lactation, milk yield and lactose content were mainly positive while a mainly negative relationship was found with a number of days after calving.